CORRELATION DEVELOPMENTAL ABNORMALITIES OF THE FACIAL SKELETON AND NARROWING OF THE UPPER AIRWAY IN PATIENTS WITH CONGENITAL SOMATIC GENETIC PATHOLOGIES - Пантус, В. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The results of study of intercommunication of underdeveloped of middle area of facial skeleton and degree of narrowing of overhead respiratory tracts are represented in the article. In this research three-dimensional сephalometry and stereotopometry analysis the з use of information of spiral computed tomographic of skull of 52 patients is conducted from 1-3, 3-7 years with innate cranial – by facial anomalies and deformations. It is shown, that developed, and also offered by us to the use in the clinic of method of сephalometry and stereotopometry analysis of middle area of facial skeleton allow to optimize diagnostics with the purpose of the subsequent planning of treatment of anomalies of development of facial skeleton.